2018
DOI: 10.1186/s12245-018-0215-6
|View full text |Cite
|
Sign up to set email alerts
|

The impact of prothrombin complex concentrates when treating DOAC-associated bleeding: a review

Abstract: BackgroundBleeding complications are a risk associated with all anticoagulants. Currently, the treatment options for the management of direct oral anticoagulant (DOAC)-associated bleeding are limited. Prothrombin complex concentrates (PCCs) have been proposed as a potential therapeutic option, and evidence regarding their use is increasing.ReviewMany studies supporting PCC have used preclinical models and healthy volunteers; however, more recently, observational studies have further improved insight into curre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
18
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 28 publications
(20 citation statements)
references
References 132 publications
(127 reference statements)
2
18
0
Order By: Relevance
“…As discussed above, anti-FXa levels were not impacted by PCCs in these studies. 17,21,28 Moreover, thrombin generation was not normalized in most cases with 4F-PCCs until the inhibitors had been substantially cleared, 21 a finding consistent with the present study showing that 4F-PCCs did not normalize TF-TG unless FXa inhibitor levels were <35-75 ng/mL (Table 2; Figure 5). Regarding bleeding patients on FXa inhibitors, several observational studies have reported on the use of 4F-PCCs but have shown inconsistent efficacy results.…”
Section: Ta B L E 2 Estimation Of Residual Fxa Activity In the Presensupporting
confidence: 88%
See 2 more Smart Citations
“…As discussed above, anti-FXa levels were not impacted by PCCs in these studies. 17,21,28 Moreover, thrombin generation was not normalized in most cases with 4F-PCCs until the inhibitors had been substantially cleared, 21 a finding consistent with the present study showing that 4F-PCCs did not normalize TF-TG unless FXa inhibitor levels were <35-75 ng/mL (Table 2; Figure 5). Regarding bleeding patients on FXa inhibitors, several observational studies have reported on the use of 4F-PCCs but have shown inconsistent efficacy results.…”
Section: Ta B L E 2 Estimation Of Residual Fxa Activity In the Presensupporting
confidence: 88%
“…Factor replacement therapies, such as four-factor prothrombin complex concentrates (4F-PCCs), are approved for reversal of anticoagulation with vitamin K antagonists (VKA; eg, warfarin) and serve to replace factors VII (FVII), IX (FIX), X (FX), and II (FII) rendered functionally deficient by the anticoagulant. 11 Although 4F-PCCs have been studied for FXa inhibitor reversal in nonclinical in vitro/ex vivo assays, [12][13][14] animal models, 15 healthy volunteers, [16][17][18][19][20][21][22][23] and observational clinical studies in patients taking FXa inhibitors, [24][25][26][27] the effectiveness and clinical benefit of 4F-PCCs on hemostatic efficacy and reversal of key biomarkers are mixed, 7,[28][29][30][31] and their potential mechanism of action has not been critically elucidated. There have been no controlled studies evaluating the effectiveness of 4F-PCCs for reversal of FXa inhibitor-mediated bleeding (or anticoagulation), and they are not approved for this indication.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Various studies have evaluated the safety and efficacy of 4F-PCCs in DOAC reversal, in settings including major bleeding and requirement for urgent surgery [27,44,[55][56][57][58][59][60][61]. 4F-PCC was generally effective in achieving hemostasis in patients with major bleeding, with TEE rates ranging from 0% to 8% [27,44,[56][57][58][59][60]62], and appeared to be associated with a mortality benefit versus no reversal treatment in patients with traumatic ICH [61]. However, one meta-analysis (including 10 case series) reported that it was difficult to assess whether the addition of 4F-PCCs was more effective in managing major bleeding compared with cessation of DOAC therapy alone [63].…”
Section: Recent Evidence For Anticoagulant Reversalmentioning
confidence: 99%
“…Moreover, some experts suggested that activated PCC (APCC, FEIBA©, Takeda, Japan) could be an effective strategy to improve haemostasis in DOAC-related major bleeding events [7,8]. Although clinical guidelines recommend PCCs for the treatment of DOAC-associated bleeding events [9], some authors suggested that PCCs may not be effective in this situation [10]. In the present study, we assessed the in vitro efficacy and safety of three 4-factor PCCs that contain the human coagulation factors II, VII, IX and X and are commercially available in France for reversing rivaroxaban anticoagulant effect.…”
mentioning
confidence: 99%